2014
DOI: 10.3389/fncel.2014.00015
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNA in motor neuron disease

Abstract: microRNA is a subset of endogenous non-coding RNA. It binds to partially complementary sequences in mRNAs and inhibits mRNA translation by either blocking translational machinery or degrading mRNAs. It is involved in various cellular processes including cell cycle, development, metabolism, and synaptic plasticity. Dysregulation of miRNA expression and function is reported in various diseases including cancer, metabolic disorders as well as neurological disorders. In nervous system, miRNA related pathways play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 98 publications
1
54
0
Order By: Relevance
“…Of particular interest, miRNA dysregulation is linked to aging and neurodegenerative disorders, including PD, AD, and multiple sclerosis (Goodall et al, 2013; Li et al, 2011; Ma et al, 2014). miRNA alterations are also present in microglial and neuronal cells in rodent ALS models and in peripheral blood mononuclear cells (PBMCs), fibroblasts, cerebrospinal fluid, and postmortem tissue from ALS subjects (Butovsky et al, 2012; Campos-Melo et al, 2013; De Felice et al, 2012; Freischmidt et al, 2014; Koval et al, 2013a; Kye and Goncalves Ido, 2014; Shinde et al, 2013), results which all support our observed DEmiRNAs in postmortem ALS spinal cord tissue. DEmiRNAs are likewise present in serum from pre-manifest fALS mutation carriers, suggesting both a role for miRNAs in ALS pathogenesis and as potential diagnostic biomarkers (Freischmidt et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…Of particular interest, miRNA dysregulation is linked to aging and neurodegenerative disorders, including PD, AD, and multiple sclerosis (Goodall et al, 2013; Li et al, 2011; Ma et al, 2014). miRNA alterations are also present in microglial and neuronal cells in rodent ALS models and in peripheral blood mononuclear cells (PBMCs), fibroblasts, cerebrospinal fluid, and postmortem tissue from ALS subjects (Butovsky et al, 2012; Campos-Melo et al, 2013; De Felice et al, 2012; Freischmidt et al, 2014; Koval et al, 2013a; Kye and Goncalves Ido, 2014; Shinde et al, 2013), results which all support our observed DEmiRNAs in postmortem ALS spinal cord tissue. DEmiRNAs are likewise present in serum from pre-manifest fALS mutation carriers, suggesting both a role for miRNAs in ALS pathogenesis and as potential diagnostic biomarkers (Freischmidt et al, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The proinflammatory cytokine IL-6 was examined as an indicator of microglial cell function. The chemokine, fractalkine (CX3CL1) and its cognate receptor (CX3CR1) were also analyzed, as recent evidence suggests that neuronally expressed CX3CL1 can modulate glutamatergic tone, inhibit microglial cell activation, and regulate the effects of chronic stress on neuronal plasticity and depressive-like behaviors through microglial CX3CR1-mediated actions (Paolicelli et al, 2014; Sheridan et al, 2014; Milior et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…In addition, mutant TDP-43 and FUS proteins may also contribute to ALS pathology by affecting the biogenesis of microRNAs, which are known to have an important role in motor neuron and NMJ function (Williams et al, 2009; Kye and Gonçalves Ido, 2014). …”
Section: Theories On the Cause(s) Of Salsmentioning
confidence: 99%